Computational and experimental investigation of a swirl nozzle for viscous fluids. (July 2020) - Laurila, E.; Koivisto, S.; Kankkunen, A.; Saari, K.; Maakala, V.; Järvinen, M.; Vuorinen, V.
Highlights: Comparison of experimental and numerical findings for a large-scale swirl nozzle. Low Reynolds number flow conditions relevant for high-viscosity, bio-mass based fuels. Inner-nozzle velocity field, discharge coefficient and spray angles are quantified. Transient characteristics of the developing air core are investigated. Predictive character of the simulation method for analyses of swirl nozzles is demonstrated. Abstract: Highly viscous flow in a large-scale pressure-swirl atomizer is studied by (1) 3d scale-resolving large-eddy simulations and volume-of-fluid method, and (2) experiments based on laser-Doppler anemometry, imaging techniques and pressure measurements. Here, a low Reynolds number regime (600 ≤  Re  ≤ 910) is investigated by varying the mass flow rate of the water-glycerol mixture. The aim of the study is to perform a comprehensive comparison between the simulations and experiments at a parameter range and nozzle geometry relevant for biomass based fuels. We report the inner-nozzle velocity profiles noting good agreement for mean velocities inside the swirl chamber between the simulations and the experiments. Consistent with the earlier work (Laurila et al., 2019 ), the simulations indicate the flow mode to be laminar with weak or non-existent gaseous core inside the swirl chamber. As revealed by both approaches, liquid film shapes after the nozzle discharge orifice are qualitatively similar, of hollow cone type, and highly unstable. Both approaches indicate linear scaling of the liquid film velocity with the inlet Reynolds number and discharge coefficients to be in the range 0.57–0.64. The experimentally measured mean opening angles are reported to be 45–62 ∘, while the numerical counterparts show reasonable correspondence with the experiments. The results demonstrate the predictive ability of the present numerical method in swirl injector analysis.